2008
DOI: 10.1007/s10096-008-0664-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the ica operon and insertion sequence IS256 among Staphylococcus epidermidis prosthetic joint infection isolates

Abstract: Joint replacement surgery has improved the quality of life for hundreds of thousands of patients. However, the infection of a joint implant is an important and serious complication, though the prevalence is low. Staphylococcus epidermidis is the most important pathogen involved in foreign-body infections. S. epidermidis is also a commensal that comprises a substantial part of the normal skin flora of humans. The possibility to demonstrate potential specific virulence markers may facilitate the interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
5
30
3
1
Order By: Relevance
“…The presence of IS256 transposon in ica locus has been reported previously (10,11,40). Results of the present study is unlike that of Conlon et al (41), which revealed that integration of IS256 to ica locus decreased the ability of strains to form biofilms.…”
Section: Discussioncontrasting
confidence: 75%
“…The presence of IS256 transposon in ica locus has been reported previously (10,11,40). Results of the present study is unlike that of Conlon et al (41), which revealed that integration of IS256 to ica locus decreased the ability of strains to form biofilms.…”
Section: Discussioncontrasting
confidence: 75%
“…2, we found two imperfect IRs flanking cfr in E. faecalis 603-50427X, suggesting that the gene may also be transferable via IS256-mediated transposition. Of note, this insertion sequence has been associated with aminoglycoside resistance (29,42) and with the ica operon in biofilm producers of Staphylococcus epidermidis (28,29). Since a high prevalence of transposons with IS256 sequences in enterococcal isolates has been reported from Japan and Thailand (70,32) and many cfr-carrying strains have been detected in the last 2 years in China (13,33,68,69,72), it is tempting to speculate that cfr has an important potential for dissemination from animals to humans in Southeast Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial adherence to orthopedic implant surfaces occurs in two essential steps (29). Its adherence to the implanted surface is followed by an accumulation process and the production of extracellular substances, such as polysaccharide intercellular adhesin (PIA) (28,47). The production of PIA is mediated by the intercellular adhesin (ica) locus, which comprises four core genes (icaA, icaB, icaC, and icaD) and a regulatory gene (icaR) (2,19,24).…”
mentioning
confidence: 99%